Co-design Center for Exascale Machine Learning Technologies (ExaLearn). (November 2021) - Alexander, Francis J; Ang, James; Bilbrey, Jenna A; Balewski, Jan; Casey, Tiernan; Chard, Ryan; Choi, Jong; Choudhury, Sutanay; Debusschere, Bert; DeGennaro, Anthony M; Dryden, Nikoli; Ellis, J Austin; et al.
Rapid growth in data, computational methods, and computing power is driving a remarkable revolution in what variously is termed machine learning (ML), statistical learning, computational learning, and artificial intelligence . In addition to highly visible successes in machine-based natural language translation, playing the game Go, and self-driving cars, these new technologies also have profound implications for computational and experimental science and engineering, as well as for the exascale computing systems that the Department of Energy (DOE) is developing to support those disciplines. Not only do these learning technologies open up exciting opportunities for scientific discovery on exascale systems, they also appear poised to have important implications for the design and use of exascale computers themselves, including high-performance computing (HPC) for ML and ML for HPC. The overarching goal of the ExaLearn co-design project is to provide exascale ML software for use by Exascale Computing Project (ECP) applications, other ECP co-design centers, and DOE experimental facilities and leadership class computing facilities.